Supporting factors in the aqidah-akhlaq teaching and learning process (study at islamic senior high schools in West-South Aceh regions) - Fedry Saputra (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
The subject of aqidah-akhlaq has a contribution in providing motivation to students to practice the values of religious belief (monotheism) and moral behavior in daily life. In this study, supporting factors in the implementation of the learning process of this subject at Islamic senior high schools (MAs) were the factors of the teachers and the environment. The research is concerned with, firstly the delivery of the teaching and learning process on the aqidah-akhlaq subject at MAs, and secondly the supporting factors of teachers in the learning process of the aqidah-akhlaq subject in MA students. This research used a qualitative approach with descriptive research method. Meanwhile, the data was collected through observation, interviews, and documentation. Research subjects were MA teachers who were in the West-South Aceh covering 5 regions: Aceh Jaya, West Aceh, Nagan Raya, Southwest Aceh, and South Aceh. The results showed that (1) there were several steps in the learning process carried out by the teachers, i.e. preparing lesson plans, delivering subject consisting of two aspects: firstly varied teaching methods and secondly varied learning media, conducting an assessment of learning outcomes, and performing follow-up efforts through individual approaches to deal with problematic students, and (2) in terms of supporting factors from both parents and society, it showed that some were supportive and some others did not care of their children.